2013
DOI: 10.4102/sajbm.v44i4.167
|View full text |Cite
|
Sign up to set email alerts
|

Building long-term marketing relationships: New perspectives on B2B financial services

Abstract: The focus of this study was on the relevance of trust, satisfaction and commitment in maintaining a long-term relationship (intention to stay) with an exchange partner in a Business-to-Business (B2B) context in the financial services industry. The perceptions of 238 B2B clients of a leading South African provider of development capital were investigated. Since support could not be found for the existence of trust, commitment and satisfaction as distinct individual dimensions, this study provides empirical supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…In the case of B2B companies, given the fact that the market competition environment has already been changed into a global competitive environment and the huge size and importance of the B2B market, more studies on active B2B transaction relations are considered necessary in the future. Existing previous studies regarding B2B transactions focused on salespersons' competence, the quality of service to improve transaction relations, and relationship marketing to maintain continuous relationships and improve transactions [5,[8][9][10]. However, there is a need for studies to understand the relationship between corporate ethical management and trust in companies or transaction commitment in establishing long-term oriented relationships in business-to-business (B2B) transactions.…”
Section: Of 18mentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of B2B companies, given the fact that the market competition environment has already been changed into a global competitive environment and the huge size and importance of the B2B market, more studies on active B2B transaction relations are considered necessary in the future. Existing previous studies regarding B2B transactions focused on salespersons' competence, the quality of service to improve transaction relations, and relationship marketing to maintain continuous relationships and improve transactions [5,[8][9][10]. However, there is a need for studies to understand the relationship between corporate ethical management and trust in companies or transaction commitment in establishing long-term oriented relationships in business-to-business (B2B) transactions.…”
Section: Of 18mentioning
confidence: 99%
“…For B2B companies, it is becoming important to establish long-term and friendly relationships with transaction partner companies to secure price competitiveness and expand the market. However, in the environment of B2B companies, it is difficult to have monopoly power due to the evolution of technology and intensifying competition [5,8]. Therefore, B2B companies are further experiencing intense competition.…”
Section: Theoretical and Empirical Background 21 B2b Transaction Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of B2B marketing in banking Theron, Terblanche and Boshoff [8] found the possibility for transformation through development of some well-established individual intentions into broader attitude as drivers of longterm relationship building in B2B sphere.…”
Section: A Literature Reviewmentioning
confidence: 99%